1997
DOI: 10.1038/sj.onc.1200978
|View full text |Cite
|
Sign up to set email alerts
|

ESX: a structurally unique Ets overexpressed early during human breast tumorigenesis

Abstract: The 430 known members of the Ets multigene family of transcriptional regulators are increasingly being recognized for their involvement in early embryonic development and late tissue maturation, directing stage-speci®c and tissue-restricted programs of target gene expression. Identi®able primarily by their 85 amino acid ETS DNAbinding domain and dispersed across all metazoan lineages into distinct subfamilies, Ets genes also produce malignancies in humans and other vertebrates when overexpressed or rearranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
186
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(197 citation statements)
references
References 20 publications
10
186
1
Order By: Relevance
“…Furthermore, ELF3 is a potent transactivator of the TGF-b II receptor that is mediated through binding to a 5'-GGAAACAGGAA-3' motif in reverse orientation at +13 to +24 in the TGF-b II receptor gene (Choi et al, 1998). The HER2/neu oncogene contains a GGAA element in its proximal promoter which is bound with high a nity by ELF3 resulting again in transactivation in breast cancer cells (Chang et al, 1997). However, in our current study we found that ELF3 acts as a transcriptional repressor in the context of the K4 promoter, an e ect that appears to be independent of binding to a classical ets site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, ELF3 is a potent transactivator of the TGF-b II receptor that is mediated through binding to a 5'-GGAAACAGGAA-3' motif in reverse orientation at +13 to +24 in the TGF-b II receptor gene (Choi et al, 1998). The HER2/neu oncogene contains a GGAA element in its proximal promoter which is bound with high a nity by ELF3 resulting again in transactivation in breast cancer cells (Chang et al, 1997). However, in our current study we found that ELF3 acts as a transcriptional repressor in the context of the K4 promoter, an e ect that appears to be independent of binding to a classical ets site.…”
Section: Discussionmentioning
confidence: 99%
“…Jen was the term designated to this novel member that resulted from screening a human foreskin keratinocyte cDNA library with a conserved 3' region of the ets domain (Andreoli et al, 1997). A search of expressed sequence tags with an 8 amino acid motif of the carboxyl terminal region of the ets domain led to the identi®cation of the same factor, termed ESX for epithelial restricted with serine box (Chang et al, 1997). The employment of a yeast two-hybrid system by screening a human placenta cDNA library again yielded the same ets factor, and was designated ERT for ets-related transcription factor (Choi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ELF3 is an example of an epithelial-speci®c ETS gene Oettgen et al, 1997;Chang et al, 1997). ELF5, similarly to ELF3, is not expressed in hematopoietic compartments, such as the thymus and spleen, but is expressed in organs such as lung, kidney, stomach and prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Transformed breast epithelial cells, for example, have been shown to express ETS family members GABPa, PEA3, ELF1, ETS1 and ELK1 (Scott et al, 1994b;DelannoyCourdent et al, 1996), but expression of these ETS family members is not restricted to epithelial cells. One ETS family member, ELF3/ESX/ESE-1/ERT, has recently emerged with epithelial and epithelial-cancer speci®c expression Chang et al, 1997;Choi et al, 1998;Oettgen et al, 1997). Given the extensive involvement of ETS factors in tumorigenesis, it becomes important to identify any additional ETS genes that may also play oncogenic roles, especially those that may be involved in epithelially derived cancers.…”
Section: Introductionmentioning
confidence: 99%